Analisis Tingkat Stres Kerja Karyawan pada PT X - Silviyani Silviyani; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the level of employee work stress at PT X by highlighting the factors that cause, impact on performance, and handling strategies undertaken. The research uses a descriptive method with a qualitative approach, through interviews, observation, and documentation. The background of this research departs from the reality of increasing work pressure in the modern world of work which has an impact on employee welfare and productivity. The results showed that work stress at PT X was triggered by the high intensity of loading and unloading activities, uneven division of workload, and discrepancies in stock data between the system and field conditions. In addition, interaction with difficult customers is also a contributing factor to stress. Nonetheless, each employee has their own mechanisms for dealing with stress, such as completing work gradually, taking breaks, listening to music, or seeking entertainment outside of working hours. The findings suggest that work stress is situational and strongly influenced by an individual's ability to manage pressure. This research is expected to contribute to the management of PT X in creating a healthier work environment and supporting employee performance.